Sustainable solution for metal electroplating of plastic product

By using a thermoplastic polymer composition for surface treatment on a polymer substrate, the health and environmental issues associated with electroplating using hexavalent chromium compounds in the prior art are solved, achieving excellent bonding and high performance between the metal layer and the polymer substrate. Impact performance.

CN119365531APending Publication Date: 2025-01-24SABIC GLOBAL TECHNOLOGIES BV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380041620.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art requires the use of hexavalent chromium compounds as etching agents when electroplating metal layers on polymer substrates, resulting in health risks, environmental pollution and high process costs.

Method used

A polymer article containing a thermoplastic polymer composition consisting of a copolymer (A), a rubber-modified thermoplastic polymer (E), a functionalized polymer (FP) and an additive mixture is made Suitable for metal plating without the use of hexavalent chromium compounds.

Benefits of technology

It achieves excellent bonding between the polymer substrate and the metal layer without using hexavalent chromium compounds, improves the adhesion of the metal layer and the impact performance of the polymer substrate, and reduces environmental pollution and process costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143129480000321
    Figure BDA0005143129480000321
  • Figure BDA0005143129480000331
    Figure BDA0005143129480000331
  • Figure BDA0005143129480000332
    Figure BDA0005143129480000332
Patent Text Reader

Abstract

The present disclosure relates to a polymer article comprising a thermoplastic polymer composition, wherein the thermoplastic polymer composition comprises (i) a copolymer (A) comprising polymer units derived from a vinyl aromatic monomer and a vinyl nitrile monomer; (ii) a rubber-modified thermoplastic polymer (E), (iii) a functionalized polymer (FP), and optionally (iv) an additive mixture. The present disclosure also relates to a surface-treated polymeric article comprising the polymeric article and a method of making such a surface-treated polymeric article. The present disclosure also relates to a plated article comprising a metal layer disposed on a polymeric substrate layer comprising a surface treated polymeric article. In addition, the invention also relates to a manufacturing method of the electroplated product.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] none. Technical Field

[0002] The present disclosure relates to the field of electroplating a metal layer on a polymer substrate, and in particular, the present disclosure relates to a metal electroplated article having a metal layer electroplated on a polymer substrate, the polymer substrate including a surface-treated polymer article, and the present disclosure also relates to a process for producing such a metal electroplated article. The present disclosure also relates to a polymer article, including a thermoplastic polymer composition, such as a composition based on acrylonitrile-butadiene-styrene (ABS) polymer, which is suitable for metal electroplating. The present disclosure also relates to a surface-treated polymer article, including the polymer article and a method for preparing the surface-treated polymer article. Background Art

[0003] When used in certain applications such as automotive applications, polymer plastic parts made from thermoplastic materials such as acrylonitrile-butadiene-styrene (ABS) resins are often metallized, where the thermoplastic material is used as a polymer substrate on which a metal coating is deposited. For example, a polymer plastic part made from ABS polymer can be coated with a metal layer to impart a mirror finish appearance similar to a metal part while maintaining the distinct advantage of light weighting as opposed to conventional metal parts. In addition, the metal coating can also improve the mechanical strength, thermal stability, and chemical resistance of the underlying polymer substrate on which the metal is coated. In this regard, ABS polymers are particularly suitable for automotive and other industrial applications due to their desirable impact properties and other useful features.

[0004] Unfortunately, many industrial practitioners often observe that metal coatings do not readily bond or adhere to most polymer-based substrates unless the surface of such polymer substrates is first chemically treated. For example, a common treatment commonly used in conventional metal electroplating processes is to chemically etch the polymer substrate with an oxidant (e.g., chromium trioxide or a mixture of chromium / sulfuric acid or chromium / sulfuric acid / phosphoric acid). These strong oxidants generally micro-roughen and chemically alter the surface of the polymer substrate by forming polar organic functional groups (e.g., R-COOH, R-OH, R--SO3, and R--CH═O) on the substrate surface. The presence of these polar groups promotes the adsorption of electroplating catalysts from aqueous solutions, which allows subsequent metal deposition to occur easily during the electroplating process. This approach allows for successful coating of metals on polymer substrates.

[0005] Conventional electroplating processes provide a strong bond between the metal layer and the polymer substrate made of ABS. A suitable indicator of the success of the bond between the metal layer and the polymer substrate is to measure the peel strength, the greater the peel strength, the better the adhesion of the metal to the polymer substrate. Therefore, etching, which is conventionally performed using hexavalent chromium trioxide, provides a treated polymer substrate with good adhesion to the metal layer.

[0006] However, the use of hexavalent chromium compounds such as chromium trioxide presents certain risks and challenges, such as 1) health risks due to the fact that such compounds are extremely carcinogenic, 2) effectively disposing of waste effluents from the etching process, which makes such etching processes not only environmentally harmful but also expensive, 3) purifying the etched plastic parts to remove any residual chromium trioxide that may be present as an impurity, as such impurities adversely affect the metal electroplating process, and 4) the use of highly oxidizing acid solutions may often damage the polymer substrate itself or render it structurally weak for metal electroplating.

[0007] In order to avoid these problems, many alternative processes to chromic acid etching have been studied in the past. For example, dry plasma etching processes have been proposed as an alternative to wet etching processes. However, the application of this method is limited to flat polymer parts. Alternatively, in the past, etching agents such as potassium permanganate have been used to try to replace chromic acid. Although the use of heated alkaline permanganate solutions has found some limited commercial success due to their slower oxidation rate compared to chromic acid, the applicability of permanganate solutions is largely limited.

[0008] As another alternative to avoid hexavalent chromium compounds during etching, it has been described in patents / patent applications such as US4415406A and EP2009142B1. Although the technical solutions described in these publications appear promising, there is still scope for further improvement of the metal plating process without the need to use hexavalent chromium compounds for etching.

[0009] Thus, exemplary embodiments of the present disclosure relate to a polymer article having excellent impact properties that can be plated with a metal layer without the use of a hexavalent chromium compound as an etchant. Some embodiments of the present disclosure relate to surface treated polymer articles that can be used as a substrate for depositing a metal layer while having excellent metal-plastic adhesion and excellent impact properties. Various embodiments of the present disclosure relate to suitable methods for surface treating polymer articles without the use of a hexavalent chromium compound as an etchant. Some embodiments of the present disclosure relate to metal-plated polymer articles having excellent bonding of a metal layer to a polymer substrate. Summary of the invention

[0010] Illustrative embodiments of the present disclosure are directed to polymeric articles comprising a thermoplastic polymer composition, wherein the thermoplastic polymer composition comprises, consists of, or consists essentially of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) comprises or consists of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%; c. a functionalized polymer (FP) present in an amount of ≥1.0 wt.% and ≤15.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥ 0.0 wt. % and ≤ 5.0 wt. %, relative to the total weight of the thermoplastic polymer composition.

[0011] Preferably, the additive mixture comprises, consists or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.The sum of components (a), (b), (c) and (d) (if present) is 100.0 wt.%.

[0012] Preferably, the polymer article comprises a thermoplastic polymer composition, wherein the thermoplastic polymer composition comprises, consists of, or consists essentially of: a. Relative to the total weight of the thermoplastic polymer composition, the copolymer (A) is present in an amount of ≥45.0 wt.% and ≤56.0 wt.%, wherein the copolymer (A) comprises or consists of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. The rubber-modified thermoplastic polymer (E) is present in an amount of ≥30.0 ​​wt.% and ≤50.0 wt.% relative to the total weight of the thermoplastic polymer composition; c. a functionalized polymer (FP) present in an amount of ≥1.0 wt.% and ≤15.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥ 0.0 wt. % and ≤ 5.0 wt. %, relative to the total weight of the thermoplastic polymer composition.

[0013] Preferably, the additive mixture comprises, consists of or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.The sum of components (a), (b), (c) and (d) (if present) is 100.0 wt.%.

[0014] In some embodiments of the present invention: a. Relative to the total weight of the thermoplastic polymer composition, the copolymer (A) is present in an amount of ≥40.0wt.% and ≤60.0wt.%, preferably ≥45.0wt.% and ≤56.0wt.%, wherein the copolymer (A) comprises or consists of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥30.0wt.% and ≤45.0wt.%, preferably ≥35.0wt.% and ≤45.0wt.%; c. the functionalized polymer (FP) is present in an amount of ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥ 1.0 wt. % and ≤ 3.0 wt. %, relative to the total weight of the thermoplastic polymer composition.

[0015] Preferably, the additive mixture comprises, consists of or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0016] Preferably, the polymer article comprises a thermoplastic polymer composition, wherein the thermoplastic polymer composition comprises, consists essentially of, or consists of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) comprises or consists of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. The rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0 wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤45.0 wt.%, preferably ≥35.0 wt.% and ≤45.0 wt.%, relative to the total weight of the thermoplastic polymer composition; c. a functionalized polymer (FP) in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥0.0 wt.% and ≤5.0 wt.%, preferably >0.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition.

[0017] Preferably, the additive mixture comprises, consists of or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0018] The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0019] It is particularly preferred that the polymer article comprises a thermoplastic polymer composition, wherein the thermoplastic polymer composition consists of or consists essentially of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) consists of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%; c. a functionalized polymer (FP) in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of >0.0 wt. % and ≤5.0 wt. % relative to the total weight of the thermoplastic polymer composition.

[0020] The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0021] Preferably, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile.Preferably, the additive mixture comprises, consists or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.

[0022] It is particularly preferred that the polymer article comprises a thermoplastic polymer composition, wherein the thermoplastic polymer composition consists of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is composed of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%; c. a functionalized polymer (FP) in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of >0.0 wt. % and ≤5.0 wt. % relative to the total weight of the thermoplastic polymer composition.

[0023] The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0024] Preferably, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile.Preferably, the additive mixture comprises, consists or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.

[0025] In some embodiments of the present disclosure, the functionalized polymer (FP) may, for example, have: a. relative to the total weight of the functionalized polymer (FP), the maleic anhydride content is ≥10.0wt.% and ≤45.0wt.%, preferably ≥15.0wt.% and ≤40.0wt.%, preferably ≥25.0wt.% and ≤35.0wt.%, preferably ≥30.0wt.% and ≤35.0wt.%; and b. When determined according to ASTM D5296-11, the weight average molecular weight is ≥1,000 g / mol and ≤25,000 g / mol, preferably ≥2,000 g / mol and ≤20,000 g / mol, preferably ≥5,000 g / mol and ≤18,000 g / mol, preferably ≥10,000 g / mol and ≤18,000 g / mol, preferably ≥12,000 g / mol and ≤18,000 g / mol.

[0026] In some embodiments of the present invention, (i) the vinyl aromatic monomer can be selected from styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene and methoxystyrene, preferably the vinyl aromatic monomer is styrene; and / or (ii) the vinyl nitrile monomer is selected from acrylonitrile, α-chloroacrylonitrile, methacrylonitrile and ethacrylonitrile, preferably the vinyl nitrile monomer is acrylonitrile. Preferably, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile.

[0027] In some embodiments of the present disclosure, the rubber-modified thermoplastic polymer (E) may, for example, include or consist of: a. a polymer rubber comprising polymer units derived from a conjugated diene, wherein the conjugated diene is selected from 1,3-butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene and any combination thereof, preferably the conjugated diene is 1,3-butadiene; and b. a grafted thermoplastic copolymer (C), wherein the grafted thermoplastic copolymer (C) is grafted to a polymer rubber, and wherein the grafted thermoplastic copolymer (C) comprises polymer units derived from: i. a vinyl aromatic monomer selected from the group consisting of styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene, methoxystyrene and any combination thereof, preferably the vinyl aromatic monomer is styrene; ii. a vinyl nitrile monomer selected from acrylonitrile, methacrylonitrile, ethacrylonitrile and any combination thereof, preferably a vinyl nitrile monomer is acrylonitrile; and iii. Optionally, a (meth) acrylic monomer selected from methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate and propyl methacrylate, preferably the (meth) acrylic monomer is methyl methacrylate (MMA); The graft thermoplastic copolymer (C) preferably comprises polymer units derived from (i) styrene, (ii) methyl methacrylate and (iii) acrylonitrile, and the polymer rubber is a polybutadiene rubber comprising polymer units derived from 1,3-butadiene.

[0028] Preferably, in some embodiments of the present disclosure, the thermoplastic polymer composition comprises, consists of, or consists essentially of: a. The copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is a styrene-acrylonitrile copolymer (SAN); b. The rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤45.0wt.%, preferably ≥35.0wt.% and ≤45.0wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with styrene / methyl methacrylate / acrylonitrile / copolymer; c. The functionalized polymer (FP) is present in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer, wherein the styrene maleic anhydride (SMA) copolymer has: i. relative to the total weight of styrene maleic anhydride (SMA) copolymer, the maleic anhydride content is ≥10.0wt.% and ≤45.0wt.%, preferably ≥15.0wt.% and ≤40.0wt.%, preferably ≥25.0wt.% and ≤35.0wt.%; and ii. when measured according to ASTM D5296-11, the weight average molecular weight is ≥1,000 g / mol and ≤25,000 g / mol, preferably ≥2,000 g / mol and ≤20,000 g / mol, preferably ≥5,000 g / mol and ≤18,000 g / mol, preferably ≥10,000 g / mol and ≤18,000 g / mol, preferably ≥12,000 g / mol and ≤18,000 g / mol; and d. The additive mixture is present in an amount of ≥0.0 wt.% and ≤5.0 wt.%, >0.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition.

[0029] Preferably, the additive mixture comprises, consists of or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate. The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0030] In some embodiments of the present disclosure, the polymeric article has: a. When measured according to ISO180 / 1A, notched Izod impact strength ≥ 15.0 kJ / m 2 And ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤30.0kJ / m 2 ; and / or b. When measured according to ASTM D7127, the average surface roughness is ≥47.0 nm and ≤200.0 nm, preferably ≥47.0 nm and ≤80.0 nm, preferably ≥47.0 nm and ≤70.0 nm.

[0031] In some embodiments of the present invention, the method for preparing the polymer article comprises the following steps: a. introducing into an extruder a group of ingredients comprising a copolymer (A), a rubber-modified thermoplastic polymer (E), a functionalized polymer and an optional mixture of additives, and obtaining an extrudable composition; b. extruding the extrudable composition under conditions of extruding and forming a group of extruded pellets; and c. Injection molding the extruded pellets under the following conditions: i. injection molding temperature ≥210.0°C and ≤250.0°C, preferably ≥215.0°C and ≤240.0°C, more preferably ≥220°C and ≤230°C; and ii. injection speed ≥10.0 mm / sec and ≤40.0 mm / sec, preferably ≥15 mm / sec and ≤35.0 mm / sec, more preferably ≥25.0 mm / sec and ≤30.0 mm / sec; and forming a polymer article.

[0032] Some embodiments of the present disclosure relate to a surface-treated polymeric article obtainable by a method comprising the steps of: a. providing a polymer article according to one or more embodiments of the present disclosure; and b. contacting at least a portion of the polymer article with a chemical agent for any period of time ≥5.0 minutes and ≤30.0 minutes, preferably ≥10.0 minutes and ≤20.0 minutes, preferably ≥15.0 minutes and ≤20.0 minutes, and at a temperature of ≥60.0°C and ≤80.0°C, preferably ≥65.0°C and ≤75.0°C, to form a surface-treated polymer article.

[0033] Preferably, the polymer article used to form the surface treated polymer article comprises a thermoplastic polymer composition, wherein the thermoplastic polymer composition consists of or consists essentially of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is composed of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%; c. a functionalized polymer (FP) in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of >0.0 wt. % and ≤5.0 wt. % based on the total weight of the thermoplastic polymer composition.

[0034] The sum of components (a), (b), (c) and (d) is 100.0 wt.%.

[0035] Preferably, the additive mixture comprises, consists of or consists essentially of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.Preferably, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile.

[0036] In some embodiments of the present disclosure, the chemical agent is a colloidal solution comprising colloidal particles of manganese oxide suspended in a mineral acid mixture comprising sulfuric acid and phosphoric acid.

[0037] In some embodiments of the present disclosure, the colloidal solution comprising colloidal particles of manganese oxide suspended in a mineral acid mixture comprises: a. The content of manganese oxide colloidal particles is ≥50.0g / L and ≤70.0g / L, preferably ≥55.0g / L and ≤65.0g / L; b. The content of phosphoric acid is ≥210.0 ml / L and ≤230.0 ml / L, preferably ≥215.0 ml / L and ≤225.0 ml / L; c. The content of sulfuric acid is ≥560.0 ml / L and ≤580.0 ml / L, preferably ≥570.0 ml / L and ≤575.0 ml / L; The total volume of the colloidal solution is 1.0 liter (L).

[0038] In some embodiments of the present disclosure, the surface treated polymeric article has: a. According to ISO180 / 1A, notched Izod impact strength ≥ 15.0 kJ / m 2 And ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤30.0kJ / m 2 ; and / or b. Determined according to ASTM D5946-17, the water contact angle of the surface-treated polymer article is ≥60.0° and ≤85.0°, preferably ≥65.0° and ≤80.0°, preferably ≥65° and ≤75°.

[0039] Some embodiments of the present disclosure relate to a metal-plated product, comprising: a. Metal layer; and b. A polymer substrate layer comprising a surface-treated polymer article according to one or more embodiments of the present disclosure; wherein the metal layer is disposed on at least a portion of the polymer substrate layer, preferably the metal layer is adhered to the treated surface of the polymer substrate layer.

[0040] In some embodiments of the present disclosure, the metal layer adheres to the treated surface of the polymer substrate layer with a peel strength of ≥0.14 N / mm, preferably ≥0.16 N / mm, preferably ≥0.2 N / mm, preferably ≥0.3 N / mm, preferably ≥0.34 N / mm, as measured according to ASTM B533-85 (2004).

[0041] Some embodiments of the present disclosure relate to a method for producing a metal-plated product, comprising the following steps: a. Providing a surface-treated polymer article according to one or more embodiments of the present disclosure; b. electrolessly plating the surface treated polymer article and forming a metal-plated precursor article; and c. contacting the metal-plated precursor article with a metal electrolyte solution for a period of ≥5 minutes and ≤35 minutes, preferably ≥25 minutes and ≤35 minutes, at any applied current ≥1.0 amp and ≤4.0 amp, preferably ≥1.0 amp and ≤3.0 amp, and forming a metal-plated article.

[0042] Some embodiments of the present disclosure relate to the use of a surface-treated polymeric article according to one or more embodiments of the present disclosure for improving the adhesion of a metal layer to a polymeric substrate in a metal-plated article. Some embodiments of the present disclosure relate to the use of a surface-treated polymeric article according to one or more embodiments of the present disclosure as a substrate suitable for receiving a metal layer.

[0043] Other objects, features and advantages of the present invention will become apparent through the following detailed description and examples. However, it should be understood that the detailed description and examples, although indicating specific embodiments of the present invention, are provided only by way of illustration and are not meant to be limiting. In addition, it is contemplated that changes and modifications within the spirit and scope of the present invention will become apparent to those skilled in the art from this detailed description. In other embodiments, features from specific embodiments may be combined with features from other embodiments. For example, features from some specific embodiments may be combined with features from any other embodiment. In other embodiments, additional features may be added to the specific embodiments described herein. DETAILED DESCRIPTION

[0044] Included below are definitions of various terms, expressions and phrases used throughout this specification.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present disclosure belongs. In this specification and the claims that follow, reference will be made to various terms that should be defined herein. All publications mentioned herein are incorporated herein by reference to disclose and describe the methods and / or materials associated with the cited publications.

[0046] When used in conjunction with the terms "comprising," "including," "containing," or "having" in the claims or specification, the use of the word "a" or "an" may mean "one," but it is also consistent with the meaning of "one or more," "at least one," and "one or more than one." The words "comprising" (and any forms of comprising, such as "including" and "comprising"), "having" (and any forms of having, such as "having" and "having"), "including" (and any forms of including, such as "including" and "including"), or "containing" (and any forms of containing, such as "containing" and "containing") are inclusive or open-ended, and do not exclude additional unrecited elements or method steps. The methods described herein may "comprise," "consist essentially of," or "consist of" specific ingredients, components, compositions, etc. disclosed throughout the specification.

[0047] The expression "polymer article" refers to an article or polymer sample produced by a process involving a molding process or an extrusion process, preferably by an injection molding process.

[0048] The expression "at least a portion" refers to parameters such as at least 25.0%, preferably at least 50.0%, preferably at least 75.0%, preferably 100.0% of the surface area.

[0049] Various embodiments of the present disclosure are based in part on the discovery that polymer articles comprising certain thermoplastic materials comprising functionalized polymers can enable metal plating of polymer articles without the need to use hexavalent chromium compounds as etchants. For example, such polymer articles can include a thermoplastic polymer composition, wherein the thermoplastic polymer composition includes, consists of, or consists essentially of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) comprises or consists of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. The rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0 wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤45.0 wt.%, preferably ≥35.0 wt.% and ≤45.0 wt.%, relative to the total weight of the thermoplastic polymer composition; c. a functionalized polymer (FP) in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥0.0 wt.% and ≤5.0 wt.%, preferably >0.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition.

[0050] Advantageously, the thermoplastic polymer composition constituting the polymer article has a purposeful composition of copolymer (A), rubber-modified thermoplastic polymer (E), functionalized polymer (FP) and an optional additive mixture, which together enable the polymer article to be surface treated for metal plating without the need to use hexavalent chromium compounds for etching. Advantageously, the polymer article has suitable impact strength, thereby allowing such polymer article to be used in the preparation of metal-plated articles suitable for various industrial applications, which require materials with excellent impact strength.

[0051] In some embodiments of the present disclosure, the polymer article comprises a thermoplastic polymer composition, which is present in an amount of ≥95.0 wt.%, preferably ≥97.0 wt.%, preferably ≥98.0 wt.%, preferably ≥99.0 wt.%, preferably 100.0 wt.%, relative to the total weight of the polymer article. Copolymer (A)

[0052] Copolymer (A) can be present in the thermoplastic polymer composition, for example, in a suitable amount. For example, copolymer (A) can be present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥36.0 wt.% and ≤65.0 wt.%, preferably ≥40.0 wt.% and ≤63.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein copolymer (A) comprises or consists of polymer units derived from (i) vinyl aromatic monomers and (ii) vinyl nitrile monomers. Preferably, copolymer (A) consists of polymer units derived from (i) vinyl aromatic monomers and (ii) vinyl nitrile monomers. In other words, copolymer (A) is derived only from vinyl aromatic monomers and vinyl nitrile monomers, and not from other monomers.

[0053] Most preferably, copolymer (A) may be present, for example, in an amount ≥45.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein copolymer (A) comprises polymer units derived from (i) vinyl aromatic monomers and (ii) vinyl nitrile monomers.

[0054] In some embodiments of the present disclosure, copolymer (A) has: relative to the total weight of copolymer (A), ≥22.0wt.% and ≤38.0wt.%, preferably ≥25.0wt.% and ≤35.0wt.%, preferably ≥30.0wt.% and ≤35.0wt.% of polymer units derived from vinyl nitrile monomers. Most preferably, copolymer (A) has: relative to the total weight of copolymer (A), ≥30.0wt.% and ≤35.0wt.% of polymer units derived from vinyl nitrile monomers.

[0055] More preferably, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile. Preferably, copolymer (A) is a styrene acrylonitrile copolymer. In a preferred embodiment of the present disclosure, copolymer (A) is a styrene acrylonitrile copolymer having ≥30.0 ​​wt.% and ≤35.0 wt.% of polymer units derived from acrylonitrile. It is particularly preferred that copolymer (A) is not a mixture of two or more different styrene acrylonitrile copolymers.

[0056] In some aspects of the present disclosure, copolymer (A) can be, for example, a terpolymer comprising or consisting of polymer units derived from (i) a vinyl aromatic monomer, (ii) a vinyl nitrile monomer, and (iii) a (meth) acrylic monomer. Vinyl aromatic monomers and vinyl nitrile monomers can be selected from monomers defined herein. (Meth) acrylic monomers can be, for example, selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, hexyl methacrylate, and decyl methacrylate. Preferably, the (meth) acrylic monomer can be methyl methacrylate (MMA). Therefore, copolymer (A) can be, for example, a terpolymer comprising polymer units derived from styrene / acrylonitrile / methyl methacrylate or α-methyl-styrene / acrylonitrile / methyl methacrylate.

[0057] The copolymer (A) may have a suitable molecular weight. For example, the average molecular weight (Mw) of the copolymer (A) is ≥50,000 g / mol and ≤100,000 g / mol, preferably ≥80,000 g / mol and ≤100,000 g / mol, preferably ≥85,000 g / mol and ≤98,000 g / mol, preferably ≥93,000 g / mol and ≤97,000 g / mol, as determined by gel permeation chromatography according to ASTM D5296-11. The determination of the molecular weight is carried out, for example, using gel permeation chromatography according to ASTM D5296-11 using tetrahydrofuran (THF) as solvent for polystyrene-based calibration.

[0058] Copolymer (A) can be selected, for example, so as to have suitable flow properties. For example, copolymer (A) can have a melt flow rate of ≥7.0 g / 10 min and ≤20.0 g / 10 min, preferably ≥8.0 g / 10 min and ≤15.0 g / 10 min, preferably ≥9.0 g / 10 min and ≤11.0 g / 10 min, as measured according to ISO 1133 (2005) at 230 ° C under a load of 1.2 kg. The inventors have found that if the melt flow rate of copolymer (A) is too high, the overall impact properties of the thermoplastic polymer composition may be adversely affected, and if the melt flow rate of copolymer (A) is too low, the desired flow properties of the thermoplastic polymer are not obtained, thereby affecting the processability of the thermoplastic polymer. Rubber modified thermoplastic polymer (E):

[0059] In one aspect of the present disclosure, the thermoplastic polymer composition comprises a suitable amount of a rubber component. The rubber-modified thermoplastic polymer (E) may be referred to as high rubber grafting or "HRG". Preferably, the thermoplastic polymer composition comprises at least 26.0 wt.% of a rubber-modified thermoplastic polymer (E). Preferably, the thermoplastic polymer composition may, for example, comprise a rubber-modified thermoplastic polymer (E) present in an amount of ≥26.0 wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤45.0 wt.%, preferably ≥35.0 wt.% and ≤45.0 wt.%, preferably ≥36.0 wt.% and ≤43.0 wt.%, relative to the total weight of the thermoplastic polymer composition.

[0060] Most preferably, the thermoplastic polymer composition has the copolymer (A) present in an amount of ≤60.0 wt.%, preferably ≤56.0 wt.%, and the rubber modified thermoplastic polymer (E) present in an amount of ≥26.0 wt.%, preferably ≥30.0 ​​wt.%, relative to the total weight of the thermoplastic polymer composition.

[0061] The rubber-modified thermoplastic polymer (E) comprises or consists of (i) a polymer rubber (ii) a grafted thermoplastic copolymer (C), wherein the grafted thermoplastic copolymer (C) is grafted to the polymer rubber. In some embodiments of the present disclosure, the polymer rubber may be a discontinuous elastomeric phase dispersed on a continuous rigid thermoplastic phase comprising the grafted thermoplastic copolymer (C), wherein at least a portion of the rigid thermoplastic phase is grafted to the discontinuous elastomeric phase.

[0062] The polymer rubber may, for example, have a suitable particle-based morphology. For example, the polymer rubber may be in the form of rubber particles having a broad unimodal particle size distribution. The polymer rubber may, for example, have an average particle size of ≥50 nanometers (nm) and ≤1000 nanometers (nm), preferably an average particle size of ≥200 nanometers (nm) and ≤500 nanometers (nm).

[0063] The rubber-modified thermoplastic polymer (E) comprises a suitable amount of polymer rubber. The rubber-modified thermoplastic polymer (E) may, for example, have a polymer rubber content of ≥55.0 wt.% and ≤75.0 wt.%, preferably ≥57.0 wt.% and ≤70.0 wt.%, preferably ≥60.0 wt.% and ≤65.0 wt.%, preferably ≥60.0 wt.% and ≤63.0 wt.%, relative to the total weight of the rubber-modified thermoplastic polymer (E). The polymer rubber content may, for example, be determined using Fourier transform infrared microspectroscopy (FT-IR).

[0064] Therefore, relative to the total weight of the rubber modified thermoplastic polymer (E), the content of the grafted thermoplastic copolymer (C) of the rubber modified thermoplastic polymer (E) is ≥25.0wt.% and ≤45.0wt.%, preferably ≥30.0wt.% and ≤43.0wt.%, preferably ≥35.0wt.% and ≤40.0wt.%, preferably ≥37.0wt.% and ≤40.0wt.%. Preferably, the rubber modified thermoplastic polymer (E) has a polymer rubber content of ≥55.0 wt.% and ≤75.0 wt.%, preferably ≥57.0 wt.% and ≤70.0 wt.%, preferably ≥60.0 wt.% and ≤65.0 wt.%, preferably ≥60.0 wt.% and ≤63.0 wt.%, relative to the total weight of the rubber modified thermoplastic polymer (E) and a grafted thermoplastic copolymer (C) content of ≥25.0 wt.% and ≤45.0 wt.%, preferably ≥30.0 ​​wt.% and ≤43.0 wt.%, preferably ≥35.0 wt.% and ≤40.0 wt.%, preferably ≥37.0 wt.% and ≤40.0 wt.%, relative to the total weight of the rubber modified thermoplastic polymer (E).

[0065] More preferably, the rubber modified thermoplastic polymer (E) has a polymer rubber content of ≥60.0 wt.% and ≤65.0 wt.%, preferably ≥60.0 wt.% and ≤63.0 wt.%, relative to the total weight of the rubber modified thermoplastic polymer (E) and a grafted thermoplastic copolymer (C) content of ≥35.0 wt.% and ≤40.0 wt.%, preferably ≥37.0 wt.% and ≤40.0 wt.%, relative to the total weight of the rubber modified thermoplastic polymer (E).

[0066] The polymerized rubber comprises polymerized units derived from a conjugated diene, wherein the conjugated diene is selected from 1,3-butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene and any combination thereof, and preferably the conjugated diene is 1,3-butadiene.

[0067] More preferably, the polymer rubber may, for example, comprise polymer units derived from a conjugated diene, for example derived from 1,3-butadiene, to form polybutadiene.

[0068] The rubber modified thermoplastic polymer (E) may for example comprise a grafted thermoplastic copolymer (C), wherein the grafted thermoplastic copolymer (C) is grafted to a polymer rubber, and wherein the grafted thermoplastic copolymer (C) comprises polymer units derived from: i. a vinyl aromatic monomer selected from the group consisting of styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene, methoxystyrene and any combination thereof, preferably the vinyl aromatic monomer is styrene; ii. an vinyl nitrile monomer selected from acrylonitrile, methacrylonitrile, ethacrylonitrile and any combination thereof, preferably the vinyl nitrile monomer is acrylonitrile; and iii. a (meth)acrylic acid monomer selected from the group consisting of methyl methacrylate, ethyl methacrylate and propyl methacrylate, preferably the (meth)acrylic acid monomer is methyl methacrylate (MMA).

[0069] Preferably, the grafted thermoplastic copolymer (C) comprises polymer units derived from styrene, methyl methacrylate and acrylonitrile, and the polymer rubber is a polybutadiene rubber comprising polymer units derived from 1,3-butadiene.

[0070] Preferably, the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with a copolymer comprising polymer units derived from styrene, methyl methacrylate, acrylonitrile.

[0071] In some embodiments of the present disclosure, the rubber-modified thermoplastic polymer (E) may include a portion of the grafted thermoplastic copolymer (C) that is not chemically grafted to the polymer rubber. The portion of the grafted thermoplastic copolymer (C) that is not chemically grafted to the polymer rubber may be referred to as "free thermoplastic copolymer (C)". For example, the rubber-modified thermoplastic polymer (E) may include ≤15.0 wt.%, preferably ≤10.0 wt.%, preferably ≤5.0 wt.%, preferably ≤2.0 wt.% of the grafted thermoplastic copolymer (C) that is not chemically grafted to the polymer rubber "free thermoplastic copolymer (C)". Functionalized polymer (FP)

[0072] The functionalized polymer (FP) is present in a suitable amount in the thermoplastic polymer composition. Relative to the total weight of the thermoplastic polymer composition, the functionalized polymer (FP) may be present, for example, in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%. The functionalized polymer (FP) is any polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer.

[0073] Preferably, the maleic anhydride content of the functionalized polymer (FP) is ≥10.0 wt.% and ≤45.0 wt.%, preferably ≥15.0 wt.% and ≤40.0 wt.%, preferably ≥25.0 wt.% and ≤35.0 wt.%, preferably ≥30.0 ​​wt.% and ≤35.0 wt.%, relative to the total weight of the functionalized polymer (FP). Preferably, the weight average molecular weight of the functionalized polymer (FP) is ≥1,000 g / mol and ≤25,000 g / mol, preferably ≥2,000 g / mol and ≤20,000 g / mol, preferably ≥5,000 g / mol and ≤18,000 g / mol, preferably ≥10,000 g / mol and ≤18,000 g / mol, preferably ≥12,000 g / mol and ≤18,000 g / mol. The molecular weight is determined, for example, using gel permeation chromatography according to ASTM D5296-11 using polystyrene-based calibration with tetrahydrofuran (THF) as solvent. Additive mixture

[0074] If present, the additive mixture may be present in the thermoplastic polymer composition, for example, in a suitable proportion. The thermoplastic polymer composition may, for example, comprise an additive mixture present in an amount of ≥0.0 wt.% and ≤5.0 wt.%, preferably >0.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition. Preferably, the additive mixture comprises or consists of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.

[0075] In some embodiments of the present disclosure, magnesium oxide (MgO) may be present, for example, in an amount of ≥0.01 wt.% and ≤0.1 wt.%, preferably ≥0.01 wt.% and ≤0.05 wt.%, relative to the total weight of the thermoplastic polymer composition. In some embodiments of the present disclosure, silicone oil may be present, for example, in an amount of ≥0.05 wt.% and ≤0.5 wt.%, preferably ≥0.1 wt.% and ≤0.5 wt.%, relative to the total weight of the thermoplastic polymer composition.

[0076] In some embodiments of the present disclosure, the wax may be present, for example, in an amount of ≥0.5 wt.% and ≤2.0 wt.%, preferably ≥0.8 wt.% and ≤1.5 wt.%, relative to the total weight of the thermoplastic polymer composition. In some embodiments of the present disclosure, magnesium stearate may be present, for example, in an amount of ≥0.05 wt.% and ≤0.5 wt.%, preferably ≥0.1 wt.% and ≤0.4 wt.%, relative to the total weight of the thermoplastic polymer composition. Polymer products

[0077] Preferably, the polymer article comprises a thermoplastic polymer composition comprising, consisting of, or consisting essentially of: a. The copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is a styrene-acrylonitrile copolymer (SAN); b. The rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤45.0wt.%, preferably ≥35.0wt.% and ≤45.0wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with styrene / methyl methacrylate / acrylonitrile / copolymer; c. The functionalized polymer (FP) is present in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer, wherein the styrene maleic anhydride (SMA) copolymer has: i. relative to the total weight of styrene maleic anhydride (SMA) copolymer, the maleic anhydride content is ≥10.0wt.% and ≤45.0wt.%, preferably ≥15.0wt.% and ≤40.0wt.%, preferably ≥25.0wt.% and ≤35.0wt.%; and ii. when measured according to ASTM D5296-11, the weight average molecular weight is ≥1,000 g / mol and ≤25,000 g / mol, preferably ≥2,000 g / mol and ≤20,000 g / mol, preferably ≥5,000 g / mol and ≤18,000 g / mol, preferably ≥10,000 g / mol and ≤18,000 g / mol, preferably ≥12,000 g / mol and ≤18,000 g / mol; and d. An additive mixture, present in an amount of ≥0.0wt.% and ≤5.0wt.%, >0.0wt.% and ≤5.0wt.%, preferably ≥1.0wt.% and ≤5.0wt.%, preferably ≥1.0wt.% and ≤3.0wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the additive mixture comprises, consists of or essentially consists of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.

[0078] Preferably, the polymer article has suitable impact properties required for certain applications including automotive parts. For example, when measured according to ISO 180 / 1A, the polymer article has ≥ 15.0 kJ / m 2 and ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 and ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 and ≤30.0kJ / m 2 Notched Izod impact strength.

[0079] Preferably, the polymer article comprises a thermoplastic polymer composition comprising, consisting of, or consisting essentially of: a. The copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is a styrene-acrylonitrile copolymer (SAN); b. The content of the rubber-modified thermoplastic polymer (E) is ≥26.0wt% and ≤50.0wt%, wherein the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with styrene / methyl methacrylate / acrylonitrile / copolymer; c. the functionalized polymer (FP) is present in an amount of ≥1.0 wt.% and ≤15.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥ 0.0 wt. % and ≤ 5.0 wt. %, relative to the total weight of the thermoplastic polymer composition.

[0080] Preferably, the additive mixture comprises, consists of, or consists essentially of magnesium oxide (MgO), silicone oil, wax, and magnesium stearate.

[0081] Preferably, the polymer article comprises a thermoplastic polymer composition comprising, consisting of, or consisting essentially of: a. The copolymer (A) is present in an amount of ≥45.0wt.% and ≤56.0wt.% relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is a styrene-acrylonitrile copolymer (SAN); b. The content of the rubber-modified thermoplastic polymer (E) is ≥35.0wt% and ≤45.0wt%, wherein the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with styrene / methyl methacrylate / acrylonitrile / copolymer; c. the functionalized polymer (FP) is present in an amount of ≥6.0 wt.% and ≤12.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥ 1.0 wt. % and ≤ 3.0 wt. %, relative to the total weight of the thermoplastic polymer composition. Method for preparing polymer article

[0082] Illustrative embodiments of the present disclosure relate to methods for producing polymer articles according to one or more embodiments of the present disclosure. The method for producing a polymer article may, for example, involve a combination of steps involving extrusion and injection molding. Preferably, the method for preparing the polymer article comprises the following steps: a. introducing into an extruder a group of ingredients comprising a copolymer (A), a rubber-modified thermoplastic polymer (E), a functionalized polymer (FP) and an optional mixture of additives to obtain an extrudable composition; b. extruding the extrudable composition under conditions of extruding and forming a group of extruded pellets; and c. Injection molding the extruded pellets under the following conditions: i. Injection temperature ≥210.0°C and ≤250.0°C, preferably ≥215.0°C and ≤240.0°C, more preferably ≥220°C and ≤230°C; ii. The injection speed is ≥10.0 mm / sec and ≤40.0 mm / sec, preferably ≥15 mm / sec and ≤35.0 mm / sec, more preferably ≥25.0 mm / sec and ≤30.0 mm / sec; and forming a polymer article.

[0083] In some embodiments of the present disclosure, the extrusion process may involve physically blending the ingredients before introducing them into the hopper of the extruder. For example, in some embodiments of the present disclosure, pellets of the functionalized polymer (FP) and copolymer A may be premixed in a container to obtain a uniformly mixed set of pellets before loading into the hopper, and then introduced into the hopper together with the preblend comprising the rubber-modified thermoplastic polymer (E) and the additive mixture.

[0084] In some embodiments of the present disclosure, once introduced into the extruder via a hopper, the physically mixed formulation can be melt blended, for example, in a 10-barrel Coperion ZSK-26 mm co-rotating twin-screw extruder with a L / D ratio of 40:1. The conditions for extrusion can, for example, include extruding at a suitable torque, at a specific mechanical energy, and at a specific RPM. Exemplary extrusion can be performed under the following conditions: (a) torque ≥30.0% and ≤75.0%, preferably ≥40.0% and ≤72.0%, more preferably ≥50.0% and ≤70.0%; (b) specific mechanical energy ≥ 0.10 KWh / Kg and ≤ 0.25 KWh / Kg, preferably ≥ 0.12 KWh / Kg and ≤ 0.22 KWh / Kg; and (c) about extrusion screw rotations per minute (RPM) ≥ 240 and ≤ 260.

[0085] In a preferred embodiment of the present invention, while maintaining the screw RPM at 250, the material throughput is adjusted to maintain between ≥8.0Kg / hour and ≤30.0Kg / hour, ≥8.0Kg / hour and ≤25.0Kg / hour, preferably maintained at a specific mechanical energy (SME) between 0.15kWh / t and 0.22kWh / t.

[0086] In some embodiments of the present invention, the injection molding temperature is ≥210.0°C and ≤250.0°C, preferably ≥215.0°C and ≤240.0°C, more preferably ≥220°C and ≤230°C, and the injection molding speed is maintained at ≥10.0mm / sec and ≤40.0mm / sec, preferably ≥15mm / sec and ≤35.0mm / sec, more preferably ≥25.0mm / sec and ≤30.0mm / sec. Surface treated polymer products

[0087] Illustrative embodiments of the present disclosure relate to surface-treated polymeric articles obtainable by a method comprising the steps of: a. providing a polymer article according to one or more embodiments of the present disclosure; and b. contacting at least a portion of the polymer article with a chemical agent for any period of time ≥5.0 minutes and ≤30.0 minutes, preferably ≥10.0 minutes and ≤20.0 minutes, preferably ≥15.0 minutes and ≤20.0 minutes, and at a temperature of ≥60.0°C and ≤80.0°C, preferably ≥65.0°C and ≤75.0°C, to form a surface-treated polymer article.

[0088] Preferably, the polymeric article used to form the surface treated polymeric article comprises a thermoplastic polymer composition, wherein the thermoplastic polymer composition consists of or consists essentially of: a. the copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.% relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is composed of polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%; c. a functionalized polymer (FP) in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), preferably the functionalized polymer (FP) is styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of >0.0 wt. % and ≤5.0 wt. % relative to the total weight of the thermoplastic polymer composition.

[0089] The surface-treated polymer article may comprise the thermoplastic polymer composition in an amount greater than 95.0 wt.%, preferably greater than 96.0 wt.%, preferably greater than 99.0 wt.%, preferably 100 wt.%, relative to the total weight of the surface-treated polymer article.

[0090] More preferably, the polymer article is contacted with the chemical agent at a temperature of ≥65.0°C and ≤75.0°C for any period of time between ≥15.0 minutes and ≤20.0 minutes. The surface treated polymer article has suitable surface polarity while maintaining the required impact strength. The properties of surface polarity and impact strength can be attributed, for example, to a purposeful combination of suitable polymer article, suitable selection of chemical agent, and suitable process parameters of temperature and time period of contact / exposure.

[0091] Illustrative embodiments of the present disclosure relate to surface-treated polymer articles comprising a polymer article according to one or more embodiments of the present disclosure, wherein the surface-treated article has a water contact angle of ≥60.0° and ≤85.0°, preferably ≥65.0° and ≤80.0°, preferably ≥65° and ≤75°, measured according to ASTM D5946-17.

[0092] Advantageously, the surface treated polymeric article has a sufficiently low water contact angle, indicating suitable surface polar functional groups that may be required for the polymeric article to adhere to the metal layer.

[0093] Preferably, the surface treated polymer article is able to maintain the impact performance of the polymer article even after surface treatment with a chemical agent. For example, when measured according to ISO 180 / 1A, the surface treated polymer article has an impact resistance of ≥ 15.0 kJ / m 2 and ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 and ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 and ≤30.0kJ / m 2 Notched Izod impact strength.

[0094] Thus, in some embodiments of the present disclosure, the surface treated polymeric article has: A. When measured according to ISO180 / 1A, the notched Izod impact strength is ≥15.0kJ / m 2 And ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤30.0kJ / m 2 ;as well as b. The water contact angle of the surface-treated polymer article is ≥60.0° and ≤85.0°, preferably ≥65.0° and ≤80.0°, preferably ≥65° and ≤75°, measured according to ASTM D5946-17.

[0095] Illustrative embodiments of the present disclosure are directed to surface-treated polymeric articles comprising a thermoplastic polymer composition, wherein the thermoplastic polymer composition comprises, consists of, or consists essentially of: a. The copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is a styrene-acrylonitrile copolymer (SAN); b. The rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤50.0wt.%, preferably ≥30.0wt.% and ≤45.0wt.%, preferably ≥35.0wt.% and ≤45.0wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with a copolymer of styrene, methyl methacrylate and acrylonitrile; c. the functionalized polymer (FP) is present in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥0.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition; wherein the surface-treated polymer article has: i. Notched Izod impact strength ≥ 15.0 kJ / m when measured according to ISO180 / 1A 2 And ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤30.0kJ / m 2 ; and / or ii. a water contact angle of ≥60.0° and ≤85.0°, preferably ≥65.0° and ≤80.0°, preferably ≥65° and ≤75°, measured according to ASTM D5946-17, further wherein the additive mixture comprises or consists of magnesium oxide (MgO), silicone oil, wax and magnesium stearate.

[0096] The present inventors have found that the water contact angle of the surface treated polymer article is lower than that of the polymer article itself, indicating improved surface wettability and thus a greater tendency to adhere to the metal layer.

[0097] Illustrative embodiments of the present disclosure relate to a method for preparing a surface-treated polymer article according to one or more embodiments of the present disclosure, wherein the method comprises the following steps: a. providing a polymer article according to one or more embodiments of the present disclosure; and b. contacting a polymer article according to one or more embodiments of the present disclosure with a chemical agent under temperature conditions of ≥60.0°C and ≤80.0°C, preferably ≥65.0°C and ≤75.0°C, for any period of time of ≥5.0 minutes and ≤30.0 minutes, preferably ≥10.0 minutes and ≤20.0 minutes, preferably ≥15.0 minutes and ≤20.0 minutes, to form a surface-treated polymer article.

[0098] Advantageously, the surface treated polymeric article is prepared without the use of hexavalent chromium compounds, thereby avoiding all the disadvantages currently associated with conventional etching processes using such hexavalent chromium compounds.

[0099] The polymer article may, for example, be contacted with the chemical agent for an appropriate period of time to ensure bonding to the desired surface roughness. For example, if the period of time that the polymer article is contacted with the chemical agent is too high (high exposure time), the surface of the polymer article may be damaged, while if the polymer article is contacted with the chemical agent for too short a time, the surface morphology of the polymer article is not sufficiently changed to enable the surface treated polymer article to adhere to the metal layer.

[0100] The chemical agent can be selected, for example, from a sulfuric acid solution having a volume concentration of 70.0%, a colloidal solution comprising manganese oxide colloidal particles suspended in an inorganic acid mixture, a potassium permanganate solution having a volume concentration of 6.5%, and any combination thereof. More preferably, the chemical agent is a colloidal solution comprising manganese oxide colloidal particles suspended in an inorganic acid mixture comprising sulfuric acid and phosphoric acid.

[0101] Preferably, the colloidal solution comprising colloidal manganese oxide particles suspended in a mineral acid mixture comprises: a. The content of manganese oxide colloidal particles is ≥50.0g / L and ≤70.0g / L, preferably ≥55.0g / L and ≤65.0g / L; b. The content of phosphoric acid is ≥210.0 ml / L and ≤230.0 ml / L, preferably ≥215.0 ml / L and ≤225.0 ml / L; c. The content of sulfuric acid is ≥560.0 ml / L and ≤580.0 ml / L, preferably ≥570.0 ml / L and ≤575.0 ml / L; The total volume of the colloidal solution is 1.0 liter (L).

[0102] The chemical reagent may, for example, include sulfuric acid (H2SO4) with a molar strength of ≥8.0M and ≤14.0M, preferably ≥9.0M and ≤12.0M. The chemical reagent may, for example, include phosphoric acid with a molar strength of ≥2.0M and ≤6.0M, preferably ≥3.0M and ≤5.0M.

[0103] The present inventors have surprisingly discovered that when the polymeric articles of the present disclosure are treated with a suitable chemical agent at a specific temperature for a specific period of time, the resulting surface treated polymeric articles have a desired surface roughness and polar functional groups comparable to polymeric surfaces etched with hexavalent chromium compounds.

[0104] In other words, the surface treated polymer article according to one or more embodiments of the present disclosure has a surface texture suitable for metal plating even without the use of a hexavalent chromium compound. For example, if the chemical agent is contacted for an exposure period of less than 5 minutes, the desired surface roughness and polar functional groups required for metal adhesion may not be obtained, while if the article is exposed to the chemical agent for an exposure time of more than 30 minutes, the surface of the plastic article may be damaged. Metal plated products

[0105] One aspect of the present disclosure relates to a metal-plated article, comprising: a. Metal layer; and b. A polymer substrate layer comprising a surface-treated polymer article according to one or more embodiments of the present disclosure; wherein the metal layer is disposed on the polymer substrate layer, preferably the metal layer is adhered to the treated surface of the polymer substrate layer. The expression "treated surface" as used herein refers to a portion of the polymer substrate layer or the surface-treated polymer article that has been exposed to a chemical agent for surface treatment.

[0106] The metal layer adheres to the treated surface of the polymer substrate layer with a peel strength of ≥0.14 N / mm, preferably ≥0.16 N / mm, preferably ≥0.2 N / mm, preferably ≥0.3 N / mm, preferably ≥0.34 N / mm, as measured according to ASTM B533-85 (2004).

[0107] Preferably, the metal layer is adhered to the treated surface of the polymer substrate layer with a peel strength of ≥0.14 N / mm and ≤2.0 N / mm, preferably ≥0.16 N / mm and ≤2.0 N / mm, preferably ≥0.2 N / mm and ≤1.5 N / mm, preferably ≥0.3 N / mm and ≤1.5 N / mm, measured according to ASTM B533-85 (2004).

[0108] Peel strength is a suitable indicator of adhesion of the polymer substrate to the metal layer. The present inventors believe that the surface treated article has suitable surface roughness and polarity which imparts the desired anchoring points on the surface of the article, making the article suitable as a polymer substrate for metal electroplating.

[0109] Surface roughness can be determined, for example, using a DektakXT contact surface profiler that uses a mechanical stylus to measure surface roughness in thin and thick films. The roughness of a surface treated polymer article can be determined, for example, using a mechanical needle having, for example, a 12.5 μm radius tip that can be lowered into contact with the article surface under a load adjustable from 1 mg to 15 mg. The article can be displaced a distance, for example up to 55 mm, in the horizontal plane toward the operator. Software, such as the Vision64 application, can be used to determine the roughness of a given article by calculating and displaying the results of the valleys of the surface texture.

[0110] The metal-plated product can be produced, for example, by a combination of chemical plating and electroplating. For example, a method for making a metal-plated product comprises the following steps: a. Providing a surface-treated polymer article according to one or more embodiments of the present disclosure; b. electrolessly plating the surface treated polymer article to form a metal-plated precursor article; and c. contacting the metal-plated precursor article with a metal electrolyte solution at any applied current of ≥ 1.0 ampere and ≤ 4.0 amperes for a period of ≥ 5 minutes and ≤ 30 minutes and forming the metal-plated article.

[0111] Chemical plating may, for example, include the following steps: (i) sensitizing the surface-treated polymer article with a suitable sensitizing solution (e.g., a solution of SnCl2 / HCl), and then activating it with an activation solution (e.g., a solution of PdCl2 / HCl) to form an activated article, and (ii) thereafter treating the activated article with monosodium phosphate (NaH2PO4) and a chemical plating solution to obtain a metal-plated precursor article.

[0112] The chemical plating solution may, for example, include CuSO4.5H2O (15 g / L), NaKC4H4O6.4H2O (30 g / L), HCHO (100 ml / L) and NaOH (4 g / L). Alternatively, the chemical plating solution may, for example, include NiSO4.6H2O (15 g / L), NaKC4H4O6.4H2O (30 g / L), HCHO (100 ml / L) and NaOH (4 g / L). The metal electrolyte may, for example, be selected from nickel sulfate, copper sulfate, aluminum salts such as aluminum chloride or aluminum sulfate, zinc-based salts such as zinc sulfate or zinc chloride, silver salts such as silver sulfate or silver chloride and a mixture of metal salts.

[0113] The chemical plating process results in the formation of a metal-plated precursor product. The metal-plated precursor product has the appropriate conductivity required for the electroplating process. The metal layer can be, for example, a copper-based layer, an aluminum-based layer, a nickel-based layer, a zinc-based layer, a gold-based layer or a silver-based layer or a metal alloy-based layer, preferably the metal layer is a copper-based layer. The metal alloy can be selected from brass, for example.

[0114] The metal plated articles may be selected, for example, from automobile parts, housing structures for electrical appliances.

[0115] The following includes specific examples demonstrating some embodiments of the present disclosure. The embodiments are for illustrative purposes only and are not intended to limit the present invention. It should be understood that the embodiments and aspects disclosed herein are not mutually exclusive, and these aspects and embodiments can be combined in any manner. Those of ordinary skill in the art will readily recognize parameters that can be changed or modified to produce substantially the same results. Example Example 1

[0116] Purpose: To demonstrate the features of the present disclosure, the following samples were prepared to evaluate the peel strength of the metal layer from the polymer substrate. The polymer samples with sample codes D13, D21 and D22 have thermoplastic polymer compositions that conform to one or more embodiments of the present disclosure, and the chemical reagent used to prepare the surface-modified polymer article is manganese oxide colloidal particles suspended in a mineral acid mixture consisting of sulfuric acid and phosphoric acid. Samples D20, D14 and EC2 are comparative samples. Sample EC2 does not contain any functionalized polymer. All samples were surface treated using the chemical reagent H3PO4 (4.2M)-H2SO4 (9.4M)-MnO2 (60g / L) colloid.

[0117] Sample materials :The various materials used are as follows: Table 1

[0118] The composition details of the samples are as follows. The total weight of all samples is 4.0 kg. Table 2

[0119] The additive mixture contained 0.04 wt.% of magnesium oxide, 0.2 wt.% of silicone oil, 1.0 wt.% of EBX wax and 0.3 wt.% of magnesium stearate, relative to the total weight of the sample.

[0120] Details of the acrylonitrile content and maleic anhydride content are provided in the following table: Table 3

[0121] Method for preparing polymer articles (sample plates): To prepare the samples, a combination of extrusion and injection molding methods was used.

[0122] Extrusion method: All formulations were prepared at 4.0 Kg scale. A mixture of styrene acrylonitrile (SAN) pellets and functionalized polymer styrene maleic anhydride (SMA) copolymer was added through a hopper / feeder while a premix of 1) rubber modified thermoplastic polymer (E) (polybutadiene rubber pellets grafted with styrene / methyl methacrylate / acrylonitrile copolymer, also known as HRG) and 2) an additive mixture comprising EBX wax, magnesium stearate, magnesium oxide and silicone fluid was added through a side feeder connected to barrel 2 of the extruder.

[0123] A control sample (EC2) was prepared by mixing equal amounts of two different grades of copolymer (A) - styrene acrylonitrile SAN556 (acrylonitrile content of 34.0 wt.%) and SAN581 (acrylonitrile content of 25.0 wt.%) without any functional additives. The granules SMA and SAN were premixed (physically mixed) together in a plastic container to obtain a homogeneous mixture of granules before loading into the hopper. Similarly, a preblend in the form of a homogeneous powder was obtained by dry blending (physically mixing) the rubber modified thermoplastic polymer (E) and the additive mixture in a separate container.

[0124] The physical mixed formulation comprising copolymer (A), rubber modified thermoplastic polymer (E), functionalized polymer was introduced into the extruder and melt blended in a 10-barrel Coperion ZSK-26 mm co-rotating twin-screw extruder with a L / D ratio of 40: 1. During the extrusion process, the material throughput was adjusted to maintain the specific mechanical energy (SME) between 0.15 KWh / Kg and 0.22 KWh / Kg while the screw RPM was maintained at 250.

[0125] The parameters of the extrusion process are shown in the following table: Table 4

[0126] For the severe screw design, this screw has additional neutral kneading blocks and a small back-conveying element, while the mild screw design has a small back-conveying kneading block. The temperature profile of the extruder barrel is as follows: Table 5 bucket <![CDATA[1 st ]]> <![CDATA[2 nd ]]> <![CDATA[3 rd ]]> <![CDATA[4 th ]]> <![CDATA[5 th ]]> <![CDATA[6 th ]]> <![CDATA[7 th ]]> <![CDATA[8 th ]]> <![CDATA[9 th ]]> <![CDATA[10 th ]]> Temperature ℃ 170 204 225 230 240 240 240 240 240 245

[0127] Injection molding process: The injection molding process was carried out in an L&T Detech 100 ton injection molding machine equipped with a 32 mm diameter screw. The molded parts were heated at 23 °C and relative humidity (R H After conditioning, all molding formulations were subjected to impact strength testing. Table 6

[0128] According to ISO 180 / 1A standard, the polymer products obtained by the molding process were tested for notched Izod impact strength. The results are as follows: Table 7

[0129] As can be seen from the above table, the polymer articles or sample plaques of the present invention prepared from the thermoplastic polymer composition according to one or more embodiments of the present disclosure have desirable impact properties.

[0130] Method for preparing a surface treated polymer article (referred to as a pre-treatment step): Once obtained from the above method, the polymer article or sample plate was contacted with a chemical reagent comprising H3PO4 (4.2M)-H2SO4 (9.4M)-MnO2 (60g / L). The treatment time period was maintained at 20 minutes and the temperature condition was maintained at 70°C to obtain a surface treated polymer article.

[0131] The water contact angle of the surface treated polymer article was measured according to ASTM D5946, and the notched Izod impact strength was measured according to ISO180 / 1A. The results are as follows: Table 8

[0132] As can be seen from Table 8, the surface treated polymer articles have the desired water contact angle and are able to maintain the desired impact resistance. Further observation shows that the water contact angle of the surface treated articles is lower than that of the starting polymer article before the pre-treatment step, indicating that its surface wettability is improved, making it more suitable for adhesion to the metal layer. For example, the water contact angle of the surface treated article made of polymer article / sample patch D22 is reduced by nearly 43% compared to the polymer article D22 before surface treatment, while the water contact angle of the surface treated article D13 is reduced by nearly 13%.

[0133] Further observations revealed that the surface morphology did not change significantly within the first 5 minutes after contact with the chemical reagent. However, as the contact time was further extended, the surface morphology changed significantly.

[0134] For example, when the molded plaques of D13 or D22 were pretreated with H3PO4 (4.2 M)-H2SO4 (9.4 M)-MnO2 (60 g / L) for 20 min, the number of surface cavities increased and the resulting shape was similar to that of a typical six-color chrome etched sample.

[0135] These findings show that treating the substrate with manganese oxide colloids in combination with high concentrations of sulfuric acid / phosphoric acid for 20 minutes resulted in the formation of numerous cavities. However, when the exposure time exceeded 30 minutes or, in some cases, 20 minutes, the polymer surface was severely damaged.

[0136] Production process of plated metal products: The surface treated polymer material is plated with a layer of metal. In this embodiment, the metal layer is a copper layer. The process of depositing a metal layer on the surface treated polymer article includes the following steps: 1) chemical plating, followed by 2) electroplating, and finally obtaining a metal-plated article.

[0137] Chemical plating process: The chemical plating process includes placing the surface-treated polymer object into a plating solution, where the metal ions in the plating solution are reduced and combined with the polar groups on the surface of the object to form a metal layer. During the chemical plating process, all samples were sensitized in a SnCl2 (10 g / L) / HCl (40 ml / L) solution (sensitizing solution) and then activated using a PdCl2 (0.25 g / L) / HCl (2.5 ml / L) solution (activating solution). After activation, the sample was treated in a chemical plating bath solution containing CuSO4·5H2O (15 g / L), NaKC4H4O6·4H2O (30 g / L), HCHO (100 ml / L) and NaOH (4 g / L) for 15 minutes to obtain a metal plating precursor object, which was then electroplated.

[0138] Electroplating process: The electroplating process includes an electrodeposition process step, where a copper layer is deposited layer by layer on the metal-plated precursor object using a MiniContact RS electroplating system. In this process, a copper-based electrolyte solution consisting of 75 g / L copper sulfate and 200 ml / L sulfuric acid is used. The current is maintained at 1.5 amperes and the temperature is 29°C. The electroplating time is maintained for 30 minutes to obtain the metal-plated object.

[0139] result: After obtaining the metal-plated articles, the degree of adhesion of the metal layer (copper layer) of each sample to the polymer substrate constituting the surface-treated polymer article was evaluated. The peel strength was measured according to ASTM B 533-85 (2004). The peel strength results are as follows:

[0140] From the above results, it can be seen that the metal electroplated product with D22 sample as the polymer substrate has the highest peel strength, indicating that the metal layer (copper) has a high adhesion to the polymer substrate. Advantageously, the polymer substrate also has excellent impact resistance, so that the plated metal product has the desired impact resistance.

[0141] The peel strength of the metallized article made from sample D13 is more than 90% higher than the peel strength of the metallized article made from sample D20 and is nearly 127% higher than the peel strength of sample EC2 (sample EC2 does not contain any functionalized polymer). Example 2 (Comparative)

[0142] Purpose: As another method, some samples were surface treated with some chemical agents different from those used in Example 1. The surface treated polymeric material thus obtained was electroplated by the same process as in Example 1. Subsequently, the peel strength of each of the obtained metal-plated articles was evaluated. The thermoplastic polymer component constituting each sample was the same as that used in Example 1.

[0143] As can be seen from the above table, when treated with agents such as 70% H2SO4, 6.5% KMnO4 or 5% KMnO4, none of the samples produced the desired surface treated polymer article having the necessary adhesion properties.

[0144] Based on the results obtained from Examples 1 and 2, it is apparent that only when a polymer article comprising a suitable thermoplastic polymer composition is surface treated with a suitable chemical agent under suitable conditions, such treatment results in a surface treated article having the desired surface roughness and morphology required for metal plastic adhesion.

Claims

1. A polymer article comprising a thermoplastic polymer composition, wherein the thermoplastic polymer composition comprises: a. a copolymer (A) is present in an amount of ≥35.0 wt.% and ≤70.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) comprises polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. a rubber-modified thermoplastic polymer (E) present in an amount of ≥26.0 wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤50.0 wt.%, relative to the total weight of the thermoplastic polymer composition; c. a functionalized polymer (FP), present in an amount of ≥1.0 wt.% and ≤15.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), and the functionalized polymer (FP) is preferably a styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥ 0.0 wt. % and ≤ 5.0 wt. %, relative to the total weight of the thermoplastic polymer composition.

2. The polymer article according to claim 1, wherein a. the copolymer (A) is present in an amount of ≥40.0 wt.% and ≤60.0 wt.%, preferably ≥45.0 wt.% and ≤56.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) comprises polymer units derived from (i) a vinyl aromatic monomer and (ii) a vinyl nitrile monomer; b. Relative to the total weight of the thermoplastic polymer composition, the rubber-modified thermoplastic polymer (E) is present in an amount of ≥30.0wt.% and ≤45.0wt.%, preferably ≥35.0wt.% and ≤45.0wt.%; c. relative to the total weight of the thermoplastic polymer composition, the functionalized polymer (FP) is present in an amount of ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, wherein the functionalized polymer (FP) is any one polymer selected from styrene maleic anhydride (SMA) copolymer or maleic anhydride grafted polystyrene (MA-g-PS), and the functionalized polymer (FP) is preferably styrene maleic anhydride (SMA) copolymer; and d. The additive mixture is present in an amount of ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition.

3. The polymer article according to claims 1-2, wherein the functionalized polymer (FP) has: a. relative to the total weight of the functionalized polymer (FP), the maleic anhydride content is ≥10.0wt.% and ≤45.0wt.%, preferably ≥15.0wt.% and ≤40.0wt.%, preferably ≥25.0wt.% and ≤35.0wt.%, preferably ≥30.0wt.% and ≤35.0wt.%; and b. The weight average molecular weight is ≥1,000 g / mol and ≤25,000 g / mol, preferably ≥2,000 g / mol and ≤20,000 g / mol, preferably ≥5,000 g / mol and ≤18,000 g / mol, preferably ≥10,000 g / mol and ≤18,000 g / mol, preferably ≥12,000 g / mol and ≤18,000 g / mol, as determined according to ASTM D5296-11.

4. The polymer article according to any one of claims 1 to 3, wherein a. The vinyl aromatic monomer is selected from styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene and p-hydroxystyrene, methoxystyrene, the vinyl aromatic monomer is preferably styrene; and / or b. The vinyl nitrile monomer is selected from acrylonitrile, α-chloroacrylonitrile, methacrylonitrile and ethacrylonitrile, the vinyl nitrile monomer is preferably acrylonitrile, Preferably, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile.

5. The polymer article according to any one of claims 1 to 4, wherein the rubber-modified thermoplastic polymer (E) comprises: a. a polymerized rubber comprising polymerized units derived from a conjugated diene, wherein the conjugated diene is selected from 1,3-butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, and any combination thereof, and the conjugated diene is preferably 1,3-butadiene; b. a grafted thermoplastic copolymer (C), wherein the grafted thermoplastic copolymer (C) is grafted to the polymeric rubber, and wherein the grafted thermoplastic copolymer (C) comprises polymer units derived from: i. a vinyl aromatic monomer selected from the group consisting of styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene, methoxystyrene and any combination thereof, wherein the vinyl aromatic monomer is preferably styrene; ii. a vinyl nitrile monomer selected from acrylonitrile, methacrylonitrile, ethacrylonitrile and any combination thereof, wherein the vinyl nitrile monomer is preferably acrylonitrile; and iii. a (meth) acrylic monomer selected from methyl methacrylate, ethyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate and propyl methacrylate, wherein the (meth) acrylic monomer is preferably methyl methacrylate (MMA); The grafted thermoplastic copolymer (C) preferably comprises polymer units derived from (i) styrene, (ii) methyl methacrylate and (iii) acrylonitrile, and the polymer rubber is a polybutadiene rubber comprising polymer units derived from 1,3-butadiene.

6. The polymer article according to any one of claims 1 to 5, wherein the thermoplastic polymer composition comprises: a. the copolymer (A) is present in an amount of ≥35.0wt.% and ≤70.0wt.%, preferably ≥40.0wt.% and ≤60.0wt.%, preferably ≥45.0wt.% and ≤56.0wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the copolymer (A) is a styrene-acrylonitrile copolymer (SAN); b. the rubber-modified thermoplastic polymer (E) is present in an amount of ≥26.0 wt.% and ≤50.0 wt.%, preferably ≥30.0 ​​wt.% and ≤45.0 wt.%, preferably ≥35.0 wt.% and ≤45.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the rubber-modified thermoplastic polymer (E) is a polybutadiene rubber grafted with styrene / methyl methacrylate / acrylonitrile / copolymer; as well as c. The functionalized polymer (FP) is present in an amount of ≥1.0 wt.% and ≤15.0 wt.%, preferably ≥3.0 wt.% and ≤12.0 wt.%, preferably ≥6.0 wt.% and ≤12.0 wt.%, relative to the total weight of the thermoplastic polymer composition, wherein the functionalized polymer (FP) is a styrene maleic anhydride (SMA) copolymer, wherein the styrene maleic anhydride (SMA) copolymer has: i. With respect to the total weight of the styrene maleic anhydride (SMA) copolymer, the maleic anhydride content is ≥10.0wt.% and ≤45.0wt.%, preferably ≥15.0wt.% and ≤40.0wt.%, preferably ≥25.0wt.% and ≤35.0wt.%; as well as ii. a weight average molecular weight of ≥1,000 g / mol and ≤25,000 g / mol, preferably ≥2,000 g / mol and ≤20,000 g / mol, preferably ≥5,000 g / mol and ≤18,000 g / mol, preferably ≥10,000 g / mol and ≤18,000 g / mol, preferably ≥12,000 g / mol and ≤18,000 g / mol, as determined according to ASTM D5296-11; and d. The additive mixture is present in an amount of ≥0.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤5.0 wt.%, preferably ≥1.0 wt.% and ≤3.0 wt.%, relative to the total weight of the thermoplastic polymer composition.

7. The method for preparing a polymer product according to any one of claims 1 to 6, comprising the following steps: a. introducing into an extruder a group of ingredients comprising a copolymer (A), a rubber-modified thermoplastic polymer (E), a functionalized polymer (FP) and an optional mixture of additives to obtain an extrudable composition; b. extruding the extrudable composition under conditions of extruding and forming a group of extruded pellets; and c. injection molding the extruded pellets under the following conditions: i. Injection temperature ≥210.0°C and ≤250.0°C, preferably ≥215.0°C and ≤240.0°C, more preferably ≥220°C and ≤230°C; ii. the injection speed is ≥10.0 mm / sec and ≤40.0 mm / sec, preferably ≥15 mm / sec and ≤35.0 mm / sec, more preferably ≥25.0 mm / sec and ≤30.0 mm / sec; and forming the polymer article.

8. A surface-treated polymer article obtained by a method comprising the following steps: a. Providing a polymer article according to any one of claims 1-6; and b. contacting at least a portion of the polymer article with a chemical agent for any period of time in the range of ≥5.0 minutes and ≤30.0 minutes, preferably ≥10.0 minutes and ≤20.0 minutes, preferably ≥15.0 minutes and ≤20.0 minutes, and at a temperature of ≥60.0°C and ≤80.0°C, preferably ≥65.0°C and ≤75.0°C, to form a surface-treated polymer article.

9. The surface-treated polymer article of claim 8, wherein the chemical agent is a colloidal solution comprising colloidal particles of manganese oxide suspended in a mineral acid mixture comprising sulfuric acid and phosphoric acid.

10. The surface-treated polymer article of claims 8-9, wherein the colloidal solution comprising colloidal particles of manganese oxide suspended in a mineral acid mixture comprises: a. The content of manganese oxide colloidal particles is ≥50.0g / L and ≤70.0g / L, preferably ≥55.0g / L and ≤65.0g / L; b. The content of phosphoric acid is ≥210.0 ml / L and ≤230.0 ml / L, preferably ≥215.0 ml / L and ≤225.0 ml / L; c. The content of sulfuric acid is ≥560.0 ml / L and ≤580.0 ml / L, preferably ≥570.0 ml / L and ≤575.0 ml / L, wherein the total volume of the colloid solution is 1.0 liter (L).

11. The surface-treated polymer article according to claims 8-10, wherein the surface-treated polymer article has: a. According to ISO180 / 1A, notched Izod impact strength ≥ 15.0 kJ / m 2 And ≤50.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤40.0kJ / m 2 , preferably ≥20.0kJ / m 2 And ≤30.0kJ / m 2 ; and / or b. Wherein, the water contact angle of the surface-treated polymer article is ≥60.0° and ≤85.0°, preferably ≥65.0° and ≤80.0°, preferably ≥65° and ≤75°, as measured according to ASTM D5946-17.

12. A metal-plated product comprising: a.Metal layer; as well as b. A polymer substrate layer comprising a surface-treated polymer article according to claims 8-11; wherein the metal layer is disposed on at least a portion of the polymer substrate layer, the metal layer preferably being adhered to the treated surface of the polymer substrate layer.

13. The metal-plated article according to claim 12, wherein the metal layer adheres to the treated surface of the polymer substrate layer with a peel strength of ≥0.14 N / mm, preferably ≥0.16 N / mm, preferably ≥0.2 N / mm, preferably ≥0.3 N / mm, preferably ≥0.34 N / mm, measured according to ASTM B533-85 (2004).

14. A method for manufacturing a metal-plated product, comprising the steps of: a. Provide a surface-treated polymer article according to claim 8-11; b. electrolessly plating the surface treated polymer article and forming a metal-plated precursor article; and c. contacting the metal-plated precursor article with a metal electrolyte solution for a period of ≥5 minutes and ≤35 minutes, preferably ≥25 minutes and ≤35 minutes, at any applied current ≥1.0 ampere and ≤4.0 ampere, preferably ≥1.0 ampere and ≤3.0 ampere, and forming a metal-plated article.

15. Use of a surface treated polymer article according to claims 8 to 11 for improving the adhesion of a metal layer to a polymer substrate in a metal plated article.

Citation Information

Patent Citations

  • Composition for etching treatment of resin molded article

    EP2009142B1

  • Chemical etching of polymers for metallizing

    US4415406A